2016
DOI: 10.18632/oncotarget.12950
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics, prognostic and predictive values of ESR1 circulating mutations in metastatic breast cancer patients progressing on aromatase inhibitor

Abstract: PurposeTo assess the prognostic and predictive value of circulating ESR1 mutation and its kinetics before and after progression on aromatase inhibitor (AI) treatment.Patients and methodsESR1 circulating D538G and Y537S/N/C mutations were retrospectively analyzed by digital droplet PCR after first-line AI failure in patients treated consecutively from 2010 to 2012 for hormone receptor-positive metastatic breast cancer. Progression-free survival (PFS) and overall survival (OS) were analyzed according to circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 28 publications
(61 reference statements)
1
54
0
5
Order By: Relevance
“…Fifteen years after this seminal discovery, many laboratories have now confirmed the presence of ESR1 mutations in MBC biopsy samples using deep sequencing, and collectively these studies have identified a hotspot for ESR1 mutations within the LBD region using various DNA sequencing methods. 9,10,12,15,16,[26][27][28] Early studies using next generation sequencing (NGS) as the detection method for ESR1 mutations found that mutations were relatively rare in clinical samples. However, the development of droplet digital PCR (ddPCR) technology has allowed for more sensitive and reliable detection of these mutations.…”
Section: Sensitive Detection Methods For Esr1 Mutations In Clinical Bmentioning
confidence: 99%
“…Fifteen years after this seminal discovery, many laboratories have now confirmed the presence of ESR1 mutations in MBC biopsy samples using deep sequencing, and collectively these studies have identified a hotspot for ESR1 mutations within the LBD region using various DNA sequencing methods. 9,10,12,15,16,[26][27][28] Early studies using next generation sequencing (NGS) as the detection method for ESR1 mutations found that mutations were relatively rare in clinical samples. However, the development of droplet digital PCR (ddPCR) technology has allowed for more sensitive and reliable detection of these mutations.…”
Section: Sensitive Detection Methods For Esr1 Mutations In Clinical Bmentioning
confidence: 99%
“…However, this same model is mostly inconsistent with the decade-long latency observed in luminal BCa. In addition, despite recent studies showed that the majority of the genetic lesions in BCa are accumulated during the early phases of tumour development 5,13 , they failed to identify any major driver associated to metastasis and resistance, with the exception of a minor fraction of cases showing either ESR1 mutations or CYP19A1 amplification [14][15][16][17] . Yet, the transcriptomes of the resistant cells are profoundly heterogeneous and different from those of the primary tumour [18][19][20] , suggesting a contribution of non-genetic mechanisms 21 .…”
Section: Introductionmentioning
confidence: 98%
“…The first question was to understand the input cfDNA quantity and quality and how it affected allele burden quantification. While several previous studies 10,38 used total amount (ng) of cfDNA as a measurement of input; for ddPCR assay, it is important to know how many copies of genomic equivalence (GE) were used as input which then sets the sample driven LOD. For example, if only 50 genomes worth of cfDNA was used as input, then even with the most sensitive assay that would detect a single mutant genome out of 50 genomes, the theoretical LOD would be 1/50 or 2%.…”
Section: Assay Performance In Clinical Samples and Impact Of Differenmentioning
confidence: 99%
“…Despite the initial effectiveness of anti-endocrine therapies, a vast majority of patients develop resistance. Although several mechanisms of resistance have been elucidated, it was only recently noted that recurrent mutations in ESR1 are enriched in ~20-40% of patients with MBC treated with an AI [3][4][5][6][7][8][9][10] . The fact that frequencies of ESR1 mutations are extremely low in primary breast tumors and enriched in metastatic tumors, supports the potential functional role of these mutations in acquired resistance to anti-endocrine therapies.…”
mentioning
confidence: 99%